AKTIVITAS ANTIOKSIDAN DARI EKSTRAK TONGKOL JAGUNG (Zea mays L.) - Saleh, Lisa Purnawati; Suryanto, Edi; Yudistira, Adithya (PHARMACON, 2012)
The objective of this research was to determine the potential antioxidant phytochemicalextracts corn cob (Zea mays L.). Corn cobs extracted using maceration method for 1x24 hours.Determination of phytochemical content is done by calculating the total phenolic. Testingantioxidant activity using free-radical scavengers DPPH (1,1-diphenyl-2-pikrilhidrazil). Results ofthis research showed that the extract of corn cobs have total phenolic. Extract 60% corn cobs haveprophylactic activity of free radicals, followed by extract 40, 80 and 20%. Conclusion of thisresearch is corn cob extracts have potential as antioxidants phytochemicals.Keywords : corn cob, antioxidant, phenolic, DPPH